Analisis Status Gizi Balita di Indonesia Tahun 2023 dengan Regresi Logistik Ordinal - Zena Azzahra Dzunnurain; Timbang Sirait (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. One of the SDGs is improved nutrition. Nutrition plays a role in maintaining the normal function of body organs, growth, and producing energy through the processes of digestion, absorption, and excretion of unused chemical substances. Undernutrition, such as underweight, stunting, wasting, micronutrient deficiencies, and overnutrition, such as overweight and excess micronutrients, are still a problem in Indonesia. This study aims to analyze the influence and tendency of the influence of the area of residence, health conditions of toddlers, father’s age, mother’s age, father’s education, mother’s education, father’s occupation, and mother’s occupation on the nutritional status of toddlers based on the W/H index in Indonesia in 2023. This study uses ordinal logistic regression to capture more detailed categories of toddler nutritional status, that is severely wasting, wasting, normal, and overweight. The results of this study indicate that the area of residence, health conditions of toddlers, informal category of father’s occupation, and all categories of mother’s occupation have an effect on the nutritional status of toddlers based on the W/H index. Abstrak. Salah satu tujuan SDGs adalah perbaikan gizi. Gizi berperan dalam mempertahankan fungsi normal organ tubuh, pertumbuhan, dan menghasilkan energi melalui proses pencernaan, penyerapan, hingga pengeluaran zat-zat kimia yang tidak digunakan. Gizi kurang, seperti underweight, stunting, wasting, defisiensi mikronutrien, dan gizi lebih, seperti overweight dan kelebihan zat gizi mikro, masih menjadi permasalahan di Indonesia. Penelitian ini bertujuan untuk menganalisis pengaruh dan kecenderungan pengaruh daerah tempat tinggal, kondisi kesehatan balita, usia ayah, usia ibu, pendidikan ayah, pendidikan ibu, pekerjaan ayah, dan pekerjaan ibu terhadap status gizi balita berdasarkan indeks BB/TB di Indonesia tahun 2023. Penelitian ini menggunakan regresi logistik ordinal dalam menangkap kategori yang lebih rinci tentang status gizi balita, yaitu severely wasting, wasting, normal, dan overweight. Hasil studi menunjukkan bahwa daerah tempat tinggal, kondisi kesehatan balita, pekerjaan ayah pada kategori informal, dan pekerjaan ibu pada semua kategori signifikan berpengaruh terhadap status gizi balita berdasarkan indeks BB/TB.